Analysis of Aggravating Factors Regarding the Theft of Sacred Religious Objects under Article 477 of Law No. 1 of 2023: An Islamic Criminal Law Perspective - Adi Fadillah; Deden Najmudin; Yusup Azazy (al-Afkar, Journal For Islamic Studies, 2026)
The evolution of criminal law in Indonesia, marked by the enactment of Law Number 1 of 2023 concerning the Criminal Code (the New KUHP), has altered the regulation of aggravated theft; the provisions previously set forth in Article 363 of the old Criminal Code have been superseded by Article 477 of the New Criminal Code. A significant update in this article is the inclusion of protection for sanctified religious objects as an aggravating factor in the crime of theft. This provision warrants examination because the theft of sanctified religious objects causes not only material loss but also impacts spiritual values, social order, and religious dignity within society. This study aims to analyze the classification of sanctified religious objects as an aggravating factor for theft under Article 477 of the Criminal Code, examine the Islamic criminal law perspective regarding this aggravating factor, and analyze the objectives of sentencing perpetrators who steal sanctified religious objects from the viewpoints of both positive law and Islamic criminal law. The study employs a normative-juridical method utilizing statutory, conceptual, and comparative approaches. The research findings indicate that sanctified religious objects possess a special legal status due to the sacred, social, and religious values they embody. Consequently, the theft of such objects merits harsher sanctions than ordinary theft. From the perspective of Islamic criminal law, this provision aligns with the objectives of maqasid al-shariʿah specifically hifz al-din (protection of religion) and hifz al-mal (protection of property) and is best understood within the framework of taʿzir as a means to protect religion and maintain social order. The novelty of this research lies in the integrative analysis of Article 477 of the New Criminal Code and the concept of jarimah sariqah in Islamic criminal law specifically regarding the classification of sanctified religious objects as an aggravating factor in theft a topic that has received limited attention in previous studies.